2016
DOI: 10.1186/s13567-016-0385-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between viral dose and outcome of infection in Atlantic salmon, Salmo salar L., post-smolts bath-challenged with salmonid alphavirus subtype 3

Abstract: Salmonid alphavirus subtype 3 (SAV3) causes pancreas disease (PD) and adversely affects salmonid aquaculture in Europe. A better understanding of disease transmission is currently needed in order to manage PD outbreaks. Here, we demonstrate the relationship between viral dose and the outcome of SAV3 infection in Atlantic salmon post-smolts using a bath challenge model. Fish were challenged at 12 °C with 3 different SAV3 doses; 139, 27 and 7 TCID50 L−1 of seawater. A dose of as little as 7 TCID50 L−1 of seawate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…There was little difference in the transcription of most of the genes between positive and negative fish at earlier sampling points (S.1) possibly because although the fish were infected, the viral replication had not yet reached a detectable level in heart tissue. Fish which tested negative by RT-qPCR could still have been viraemic, as previously demonstrated [22,32]. Moreover, both infected groups reached 100% prevalence at later time-points indicating that all fish were infected and were responding with individual variance.…”
Section: Sav Statussupporting
confidence: 64%
See 1 more Smart Citation
“…There was little difference in the transcription of most of the genes between positive and negative fish at earlier sampling points (S.1) possibly because although the fish were infected, the viral replication had not yet reached a detectable level in heart tissue. Fish which tested negative by RT-qPCR could still have been viraemic, as previously demonstrated [22,32]. Moreover, both infected groups reached 100% prevalence at later time-points indicating that all fish were infected and were responding with individual variance.…”
Section: Sav Statussupporting
confidence: 64%
“…In order to evaluate the immune response in all its complexities it is clearly advantageous to have an infection model with a synchronized time-of-infection which is of sufficient infectivity to achieve 100% prevalence during the initial stage of infection. Lower doses in an infection model cause a staggered rather than a synchronized infection due to infected fish shedding virus and exposing naïve fish not infected at time zero [32]. This makes it difficult to relate the immune response to the time of infection.…”
Section: Sav Statusmentioning
confidence: 99%
“…with either 10 4 TCID 50 SAV3 This is based on testing of different doses in the dose range over time while studying infection dynamics with SAV3 in our laboratory over several years, and in particular in two previously published studies. In these earlier studies, both a five times difference in dose (Jarungsriapisit, Moore, Maehle, et al, 2016) and larger fish with a reduced dose (Moore, Nilsen, et al, 2017) had no impact on the progression of histopathological changes, and thus, we could directly compare the two phases. Fish were anaesthetized using both a sedative, 10 mg/l metomidate, and an anaesthetic, 60 mg/l benzocaine, before handling and euthanized with 10 mg/l metomidate and 160 mg/l of Benzocaine before sampling.…”
Section: Fish and Study Designmentioning
confidence: 97%
“…Empirical and theoretical studies in other systems have suggested that viral infection kinetics and synchrony can be dose dependent (Cummings et al 2012, Littwitz-Salomon et al 2017. Viruses may take longer to initiate infection and reach peak values at lower dosages compared to higher dosages (Chu & Volety 1997, Cummings et al 2012, Abdoli et al 2013, Jarungsriapisit et al 2016. This is further supported by our finding that peak shedding shifted from 48 h post immersion in fish challenged with virus grown in cell culture (P 0 ) to 72 h in fish exposed to virus shed from other fish (P 1 −P 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by our finding that peak shedding shifted from 48 h post immersion in fish challenged with virus grown in cell culture (P 0 ) to 72 h in fish exposed to virus shed from other fish (P 1 −P 3 ). In addition, host clearance may be faster at lower virus exposure doses (Jarungsriapisit et al 2016).…”
Section: Discussionmentioning
confidence: 99%